The Application of UHPLC-HRMS for Quality Control of Traditional Chinese Medicine - Ma, Jieyao; Li, Kailin; Shi, Silin; Li, Jian; Tang, Sunv; Liu, LiangHong (Frontiers in Pharmacology, 2022)
UHPLC-HRMS (ultra-high-performance liquid chromatography-high resolution mass spectrometry) is a new technique that unifies the application of UHPLC with HRMS. Because of the high sensitivity and good separation ability of UHPLC and the sensitivity of HRMS, this technique has been widely used for structure identification, quantitative determination, fingerprint analysis, and elucidation of the mechanisms of action of traditional Chinese medicines (TCMs) in recent years. This review mainly outlines the advantages of using UHPLC-HRMS and provides a survey of the research advances on UHPLC-HRMS for the quality control of TCMs.